Ethnic Regional Networks and Immigrants' Earnings: A Spatial Autoregressive Network Approach - Xingang Wang; Sholeh A. Maani (Institute of Labor Economics (IZA), 2021)
The conventional model of immigrant earnings does not account for the correlation of outcomes across immigrant ethnic networks. We apply a spatial autoregressive network approach to account for the spill-over effects of migrant ethnic group economic resources and labour market outcomes. We employ unit-record data across 10 years for New Zealand, a major immigrant receiving country. By applying generalised method of moment (GMM) estimation, we address endogeneity of the spatial network variable. Results confirm strong positive associations of earnings with both ethnic concentration and networks of resources. The analytically enhanced approach provides opportunities for new research on the determinants of immigrant earnings.
Keywords: J30; J31; Z13; Z18; 330; earnings; ethnic network; immigrant; spatial autoregressive model; GMM estimation